2014
DOI: 10.1155/2014/731073
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Properties of Nanolamellar MoS2 Doped with Copper Nanoparticles

Abstract: This study aimed at examining the tribological properties of nanolamellar molybdenum disulfide doped with copper nanoparticles. Nanolamellar molybdenum disulfide was produced using self-propagating high-temperature synthesis via the reaction between elementary sulfur and nanosized molybdenum powder prepared by electrical explosion of wires. Copper nanoparticles were also prepared by electrical explosion of copper wires. Comparative tribological tests were carried out for nanolamellar and commercial molybdenum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Here, Xia et al [7] have shown that MoS 2 layers doped with Cu ions are ferromagnetic and display a high Curie temperature, which is rather surprising given that Cu is non-magnetic, but is in accord with earlier theoretical predictions [8,9]. Other areas where the combination of Cu and MoS 2 shows promise are tribology (enhanced wear resistance) [10,11], and electrocatalysis (hydrogen evolution reaction) [12].…”
Section: Introductionsupporting
confidence: 66%
“…Here, Xia et al [7] have shown that MoS 2 layers doped with Cu ions are ferromagnetic and display a high Curie temperature, which is rather surprising given that Cu is non-magnetic, but is in accord with earlier theoretical predictions [8,9]. Other areas where the combination of Cu and MoS 2 shows promise are tribology (enhanced wear resistance) [10,11], and electrocatalysis (hydrogen evolution reaction) [12].…”
Section: Introductionsupporting
confidence: 66%
“…
biomedicine, [2,3] tribology, [4] photonics, [5] and electrocatalysis, [6] among others. Significant progress has been made recently in fabricating and functionalizing 2D nanosheets of transition metal dichalcogenides.
…”
mentioning
confidence: 99%
“…Nanopowders produced by EEW reveal higher chemical reactivity (An et al 2010 ), unusual physicochemical properties (An et al 2011 ), can be used for fabrication of nanostructured compounds (Bozheyev et al 2014 ) and for other applications (An and Irtegov 2014 ). In the present work, alumina nanopowders produced by electrical explosion of alumina wires were used in the experiments of spark plasma sintering.…”
Section: Methodsmentioning
confidence: 99%